2020
DOI: 10.1097/bco.0000000000000953
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of efficacy of viscosupplementation for the treatment of hip osteoarthritis: a retrospective cohort study

Abstract: Background: Hip injections of hyaluronic acid (HA) have been used off-label to treat osteoarthritis (OA). The purpose of this retrospective cohort study of adults with OA was to review predictive factors and duration of action for patients who responded to HA hip injections. Methods: After institutional review board (IRB) approval, patients who had HA hip injections from 2014 to 2018 were retrospectively reviewed. Visual analog scale (VAS) scores obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Our results support UGIs with high-molecular-weight HA as a treatment for the early stages of hip OA such as reported by Kim et al [33] in selected patients. These authors showed improvements in clinical score in the first months after the injection in younger patients and those affected by mild to moderate arthritis, and negative outcomes in the older and those with more severe Kellgreen-Lawrence grading.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results support UGIs with high-molecular-weight HA as a treatment for the early stages of hip OA such as reported by Kim et al [33] in selected patients. These authors showed improvements in clinical score in the first months after the injection in younger patients and those affected by mild to moderate arthritis, and negative outcomes in the older and those with more severe Kellgreen-Lawrence grading.…”
Section: Discussionsupporting
confidence: 92%
“…HA is being administrated into OA patients via two main ways: either oral administration or local injection [31,32]. Several preparations of injectable HA used for clinical use include Synvisc ® and Synvisc-One ® (Genzyme, Corporation, Ridgefield, NJ, USA); Gel-One ® (Zimmer, Seigakaku Corporation, Cambridge, MA, USA); Hyalubrix ® (Fidia Farmaceutici, Spa-Abano Terme (PD), Italy); Supartz FX™(Bioventus, Durham, NC, USA); Orthovisc ® (Anika Therapeutics, Bedford, MA, USA); Euflexxa ® , previously named Nuflexxa (Savient Pharmaceuticals, Inc., Bridgewater, NJ, USA); Monovisc ® (Anika Therapeutics, Bedford, MA, USA); and Gel-Syn™ (Institut Biochimique SA, Pambio-Noranco, Switzerland) [33]. Each product differs in many characteristics, including source (animal vs. bacterial biofermentation using modified organisms), mean molecular weight ranging from (500 to 6000 kDa), distribution of molecular weight, molecular structure (linear, cross-linked or both), method of crosslinking, concentration (0.8-30 mg/mL), volume of injection (0.5-6.0 mL), and posology [34], although animal source of HA (rooster combs) was considered as a traditional source for many years.…”
Section: Discussionmentioning
confidence: 99%